Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the point where equations $x=t^2-t$ and $y= t^3 -3t-1$ cross itself.

This's the first time I meet this kind of problem, can someone give me some idea? Thank you.

share|cite|improve this question
which mean the two solutions of $t^2-t = p$ are solutions to $t^3-3t-1=q$,for some $p,q$. – Yimin Mar 23 '13 at 4:14
Why use new symbols (p,q)? Given (x,y) not sufficient? – Narasimham Dec 25 '14 at 19:00
up vote 2 down vote accepted

Well, what you basically need to do is find $t_1$ and $t_2$ such that $x(t_1)=x(t_2)$ and $y(t_1)=y(t_2)$, with $t_1 \neq t_2$.

To help you a little further - if you examine one of the two equations, you'll get a polynomial in $t_1$ and $t_2$ that must be divisible by $t_1-t_2$. Divide out that factor and you'll have a lower-order polynomial - solve for either $t_1$ or $t_2$, and substitute the result into the other equation. Then you'll end up with a polynomial in just one of the two values of $t$.

One solution must be the solution to $t_1=t_2$, so factor that solution out. Now solutions will exist in pairs ($t_1=a$, $t2=b$ and $t_1=b$, $t_2=a$), so it should be fairly easy to find them from there.

share|cite|improve this answer

There are some $p,q$ such that

$t^2-t = p$


has two different solutions $t_1,t_2$,

consider the third solution to the second equation as $t_3$, then $t_1+t_2+t_3 = 0$[why?]. And from the first equation $t_1+t_2 = 1$, thus $t_3 =-1$, plug into the second equation,

$(-1)^3-3*(-1)-1 = q = 1$,

then $t^3-3t-2 = (t+1)(t-2)(t+1)$, then $t_1 =2, t_2=-1$, therefore $p = 2$.

share|cite|improve this answer

As Glen has identified $t_2\ne t_1$

$$t_2^2-t_2=t_1^2-t_1\implies(t_2-t_1)(t_2+t_1)=t_2-t_1$$ $$\implies t_2+t_1=1\text{ as } t_2\ne t_1$$

$$t_2^3-3t_2-1=t_1^3-3t_1-1\implies t_2^3-t_1^3=3(t_2-t_1)$$ $$\implies t_1^2+t_1t_2+t_2^2=3\text{ as } t_2\ne t_1$$ $$\implies (t_1+t_2)^2-t_1t_2=3\implies t_1t_2=-2$$

So, $t_1,t_2$ are the roots of the Quadratic Equation $y^2-(1)y+(-2)=0\implies y=\frac{1\pm\sqrt{1^2-4(1)(-2)}}2=\frac{1\pm3}2=2,-1$

So, $t_1,t_2$ are $2,-1$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.